Hagiography as Source: Gender and Conversion Narratives in The Book of the Saints of the Ethiopian Church - Anna Redhair Wells (Religions, 2020)
Drawing on the work of Jeanne-Nicole Mellon Saint-Laurent, this essay proposes utilizing hagiographies from the The Book of the Saints of the Ethiopian Church, a fifteenth-century Ethiopian collection of saints’ lives, to explore various aspects of conversion. Other scholars employ a similar approach when analyzing hagiographical literature found in medieval Europe. While acknowledging that these texts do not provide details about the historical experience of conversion, they can assist scholars in understanding the conception of conversion in the imagination of the culture that created them. This essay specifically focuses on the role of women in conversion throughout the text and argues that, although men and women were almost equally represented as agents of conversion, a closer examination reveals that their participation remained gendered. Women more frequently converted someone with whom they had a prior relationship, especially a member of their familial network. Significantly, these observations mirror the patterns uncovered by contemporary scholars such as Dana Robert, who notes how women contributed to the spread of Christianity primarily through human relationships. By integrating these representations of conversion from late medieval Ethiopia, scholarship will gain a more robust picture of conversion in Africa more broadly and widen its understanding of world Christianity.